Properties of Optical Data from Activated Partial Thromboplastin Time and Prothrombin Time Assays - Braun, Paul J; Givens, Thomas B; Stead, Andrew G; Beck, Lisa R; Gooch, Sheila A; Swan, Robert J; Fischer, Timothy J (Thrombosis and Haemostasis, 1997)
Changes in characteristics of optical transmittance data from coagulation assays were examined as a function of concentration of coagulation proteins or anticoagulants. Transmittance data were collected for activated partial thromboplastin time (APTT) and prothrombin time (PT) assays from: 1) plasmas prepared by mixing normal plasmas with deficient plasmas to give varying levels of coagulation proteins; 2) plasmas containing added heparin; and 3) 200 specimen plasmas that were also assayed for fibrinogen, coagulation factors, and other components. Optical profiles were characterized using a set of parameters describing onset and completion of coagulation, magnitude of signal change, rate of coagulation and other properties. Results indicated that parameters other than those typically reported for APTT and PT are associated with individual deficiencies, but that diagnosis of specimen status on the basis of optical data is complex. These results suggest possibilities for expanded interpretation of PT/APTT optical data for clinical or research applications.